Preventing stillbirth from obstructed labor: A sensorized, low-cost device to train in safer operative birth - Jaufuraully, Shireen; Salvadores Fernandez, Carmen; Bagchi, Biswajoy; Gupta, Priya; Desjardins, Adrien; Siassakos, Dimitrios; David, Anna L.; Tiwari, Manish K. (Frontiers in Global Women's Health, 2023)
Background 98% of stillbirths occur in low- and middle- income countries. Obstructed labor is a common cause for both neonatal and maternal mortality, with a lack of skilled birth attendants one of the main reasons for the reduction in operative vaginal birth, especially in low- and middle- income countries. We introduce a low cost, sensorized, wearable device for digital vaginal examination to facilitate accurate assessment of fetal position and force applied to the fetal head, to aid training in safe operative vaginal birth. Methods The device consists of flexible pressure/force sensors mounted onto the fingertips of a surgical glove. Phantoms of the neonatal head were developed to replicate sutures. An Obstetrician tested the device on the phantoms by performing a mock vaginal examination at full dilatation. Data was recorded and signals interpreted. Software was developed so that the glove can be used with a simple smartphone app. A patient and public involvement panel was consulted on the glove design and functionality. Results The sensors achieved a 20 Newton force range and a 0.1 Newton sensitivity, leading to 100% accuracy in detecting fetal sutures, including when different degrees of molding or caput were present. They also detected sutures and force applied with a second sterile surgical glove on top. The software developed allowed a force threshold to be set, alerting the clinician when excessive force is applied. Patient and public involvement panels welcomed the device with great enthusiasm. Feedback indicated that women would accept, and prefer, clinicians to use the device if it could improve safety and reduce the number of vaginal examinations required. Conclusion Under phantom conditions to simulate the fetal head in labor, the novel sensorized glove can accurately determine fetal sutures and provide real-time force readings, to support safer clinical training and practice in operative birth. The glove is low cost (approximately 1 USD). Software is being developed so fetal position and force readings can be displayed on a mobile phone. Although substantial steps in clinical translation are required, the glove has the potential to support efforts to reduce the number of stillbirths and maternal deaths secondary to obstructed labor in low- and -middle income countries.